Growth habit and optical properties of γ-CuI single crystals via a temperature difference method. Issue 87 (20th September 2015) - Lv, Yangyang; Ye, Liwang; Zhang, Zhaojun; Zhang, Bin-Bin; Xu, Zhihuang; Zhuang, Xinxin; Yao, Shuhua; Su, Genbo
<x xml:space="preserve">Abstract</x> A home-designed temperature difference method was developed and used to grow γ-CuI single crystals, resulting in a great improvement for the luminescence performance of γ-CuI crystals.